Interaction of Heritable and Estrogen-induced Thrombophilia: Possible Etiologies for Ischemic Optic Neuropathy and Ischemic Stroke - Glueck, Charles J.; Fontaine, Robert N.; Wang, Ping (Thrombosis and Haemostasis, 2001)
Our specific aim was to assess how thrombophilic exogenous estrogens interacted with heritable thrombophilias leading to nonarteritic ischemic optic neuropathy (NAION) and ischemic stroke. Coagulation measures were performed in a 74 year old patient and her immediate family. The proband had a 47 year history of 9 previous thrombotic episodes, and developed unilateral NAION 4 years after starting estrogen replacement therapy (ERT). The proband was heterozygous for two thrombophilic gene mutations (G20210A prothrombin gene, platelet glycoprotein IIIa PlA1/A2 polymorphism), and homozygous for the C677T mutation in the methylenetetrahydrofolate reductase (MTHFR) gene. Of 238 normal controls, none had these 3 gene mutations together. The proband’s mother and brother had deep venous thrombosis (DVT). The proband’s brother, sister, nephew, daughter, and two granddaughters were homozygous for the C677T MTHFR mutation. The proband’s brother was heterozygous for the G20210A prothrombin gene mutation. The proband’s niece was heterozygous for the G20210A prothrombin gene mutation, homozygous for the C677T MTHFR mutation, homozygous for the hypofibrinolytic 4G polymorphism of the plasminogen activator inhibitor-1 (PAI-1) gene, and heterozygous for the platelet glycoprotein IIIa PlA1/A2 polymorphism. Of 238 normal controls, none had the niece’s combination of 4 gene mutations. When ERT-mediated thrombophilia was superimposed on the proband’s heritable thrombophilias, unilateral ischemic optic neuropathy developed, her tenth thrombotic event over a 5 decade period. When estrogenprogestin oral contraceptives were given to the proband’s niece, she had an ischemic stroke at age 22. Exogenous estrogen-mediated thrombophilia superimposed on heritable thrombophilia and hypofibrinolysis is associated with arterial and venous thrombi, and appears to be a preventable, and potentially reversible etiology for ischemic optic neuropathy and ischemic stroke.
Keywords: Thrombophilia; G20210A prothrombin gene mutation; non-arteritic ischemic optic neuropathy; ischemic stroke; estrogen